VACCINE HESITANCY OF PARENTS AND FAMILY MEMBERS OF CHILDREN AND THE CONTROL OF IMMUNOPREVENTABLE DISEASES - Izabella da Silva Viana; Emília Gallindo Cursino; Priscila da Silva Miranda; Liliane Faria da Silva; Maria Estela Diniz Machado (Cogitare Enfermagem, 2023)
Objective: to analyze, in scientific productions, the reasons that lead parents and family members of children to vaccine hesitancy in the context of control of immunopreventable diseases.